Review of Islamic Education Management Research in Schools - Mualifah, Lisna; Warisno, Andi; Ansori, Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to describe and conclude the results of Islamic education management studies for the period 2015 to 2022. This is qualitative-library research. Researchers conducted research on the results of research in journals related to the management of Islamic education in schools/madrasas from 2015-2022. The data and research data sources are in the form of "ten studies with the theme of MPI in madrasah schools”. Data sources were obtained from e-journals accessed from Google Scholar, ScienceDirect, and Elsevier. The sources sought are research results from 2015 to 2022. Data collection techniques use data collection by gathering as much information and data related to MPI. Using content analysis data analysis method. Based on a review of several studies on Islamic education management, researchers concluded that the success of Islamic education management is largely determined by the success of the human resources in it, both leaders, teachers, employees, or the community around the school/madrasah to achieve effective and efficient education. In this case, good management is needed in accordance with the rules and teachings contained in the Al-Qur'an and Hadith, while the management process of Islamic education includes planning Islamic education management, organizing Islamic education management, actuating Islamic education management, and controlling Islamic education management. In addition, in Islamic education management, there are Islamic education management principles that can be applied as a basis for decision-making.